Phytochemical Profiling and In-vitro Assessment of Antiproliferative Effects of Extracts of Freshwater Microalgae, Poterioochromonas malhamensis (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
The development of anticancer drugs remains a formidable challenge. Poterioochromonas malhamensis, known for its predatory nature on microbes and plankton, was investigated for anticancer properties. This study screened and quantified phytochemicals using LC-MS and evaluated the anticancer effects of aqueous ethanol extracts of P. malhamensis from Tavanampalli's freshwater bodies. Phytochemical analysis by HR-LCMS detected proteins, phenols, flavonoids, and alkaloids. The extract contained 87.75 mg of quercetin equivalents, 134.55 mg of gallic acid equivalents, and 72.64 mg of bovine serum albumin equivalents per gram of dry weight. LC-MS also identified amino acids, fatty acids, amides, and esters in the extract. Antiproliferative activity was assessed using MTT assay, AO/ETBR, and Annexin V/Propidium iodide (PI) staining assays. The extract exhibited IC50 values of 95.09 µg, 103.63 µg, 162.14 µg, 339.30 µg, and 355.18 µg with A375, HepG2, HeLa, HT29, and A549 cell lines, respectively, outperforming cisplatin, which had IC50 values of 3.56 µg, 4.87 µg, 3.88 µg, 7.23 µg, and 4.65 µg. This study is the first to report the antiproliferative activity of P. malhamensis, broadening the scope of research in anticancer compound discovery.